Non-typhoidal Salmonella intestinal carriage in a Schistosoma mansoni endemic community in a rural area of the Democratic Republic of Congo. - Lisette Mbuyi-Kalonji; Barbara Barbé; Gaëlle Nkoji; Joule Madinga; Clémentine Roucher; Sylvie Linsuke; Marie Hermy; Anne-Sophie Heroes; Wesley Mattheus; Katja Polman; Pascal Lutumba; Marie-France Phoba; et al. (PLOS Neglected Tropical Diseases, 2020)
BACKGROUND:Clinical observations and animal studies have suggested that Salmonella intestinal carriage is promoted by concurrent Schistosoma infection. The present study assessed association of Salmonella intestinal carriage and Schistosoma mansoni infection among individuals in a Schistosoma endemic area in sub-Saharan Africa. METHODS:From November 2015 to March 2016, a cross-sectional community-wide study was conducted in Kifua II, a rural village in Kongo Central Province, Democratic Republic of Congo. Stool samples were collected and analyzed for Salmonella intestinal carriage (culture) and Schistosoma mansoni infection (Kato Katz microscopy with determination of egg load). Salmonella Typhimurium and Enteritidis isolates were assessed for genetic similarity with blood culture isolates obtained during the same period in a neighboring hospital using multi-locus variable-numbers tandem repeat analysis (MLVA). RESULTS:A total of 1,108 participants were included (median age 15 years (IQR: 7-36), male-to-female ratio of 1:1.1). The overall prevalence of Schistosoma mansoni infection and non-typhoidal Salmonella carriage was 51.2% (95% CI: 48.2-54.1) and 3.4% (95% CI: 2.5-4.7) respectively, with 2.2% (95% CI: 1.5-3.2) of participants coinfected. The proportion of Salmonella carriage tended to be higher among Schistosoma mansoni infected participants compared to non-infected participants but this difference did not reach statistical significance (4.2% versus 2.6%, p = 0.132). However, the proportion of Salmonella carriage among participants with a heavy Schistosoma mansoni infection was significantly higher compared to those with a light and moderate infection (8.7% versus 3.2%, p = 0.012) and compared to Schistosoma mansoni negatives (8.7% versus 2.6%, p = 0.002). The 38 Salmonella isolates comprised five and four Enteritidis and Typhimurium serotypes respectively, the majority of them had MLVA types identical or similar to those observed among blood culture isolates. CONCLUSION:Salmonella intestinal carriage was ...